Urban Innovation: At the nexus of entrepreneurship and urban policy - Robinson,Jeffrey A; Joshi,Amol; Vickerie-Dearman,Lutisha; Inouye,Todd M (2019)
We define urban innovation as the development of long-lasting transformations in urban communities, neighborhoods, and cities. In our proposed framework, urban innovation is driven by two overarching principles: social inclusion and transformation. Inclusion allows for interaction across social groups and benefits society by reducing socio-economic separation through fostering stronger, and even new, relationships in the community. Transformation means deep-seated change that remodels the mindset and creates new change agents. These principles enable us to isolate innovative activities that are small and incremental, from urban innovations that have the potential to impact the economy and society in major ways. We identify three distinct types of transformative and inclusive policy innovations used in the urban innovation context: market creating, market integration, and market incentivizing. We also present three types of business model innovations that work within these innovations: social entrepreneurship, technology and innovation parks, and venture accelerators. We further categorize the social entrepreneurship business model into sustainable or triple bottom line businesses, social enterprises, micro-finance organizations and benefits corporations/B-Corps. We highlight specific examples of these policy and business model innovations from around the world to illustrate how and why urban innovations are essential for economic growth and social development in rapidly urbanizing cities. We also present several promising avenues for new research on urban innovation to guide scholars, practitioners, and policymakers in more systematically studying the phenomenon and in making strategic decisions about critical issues related to future of the world’s cities.
Keywords: Strategy & Entrepreneurship